Hubungan Senam Kegel Pada Ibu Hamil Primigravida TM III Terhadap Derajat Robekan Perineum Di Wilayah Puskesmas Pembantu Bandar Kidul Kota Kediri - Shinta Kristianti; Yohanita Putriyana (Akademi Keperawatan Dharma Husada Kediri, 2015)
Chiilddbirt injuries often result in the birtht canal, or tearing of the perineum or perineum rupture. Perineum laceration can be caused by maternal parity, estimated fetal weight, and so on becaused the perineum is elastic, but can also be found on the perineum rigid, especially on the first pregnancy (primigravida). Doing Kegel exercises can increase elastisitasion maternal perineum area. Kegel exercises to strengthen pelvic muscles before delivery, and can flex muscle of perineum as delivery baby. The purpose of this study was to determine the relationship of kegel exercises for pregnant women primigravida TM III with the degree of rupture perineum on normal deliveries at Puskesmas Bandar Kidul district of kediri. The design of this study using Analitic Correlation study with cross- sectional approach. Population from this study were 19 respondent and Samples were 16 respondents pregnant women primigravida TM III with Consecutive Sampling. Instrument in this study using a cheklist sheet and observation sheets. From the result, the results of most respondents do kegel exercise with frequency =5x each day. From the analysis of the data using the Spearman Rank r count showed 0.12 < t table 0.506 means Ho received no relationship kegel exercise with degree of rupture perineum in Puskesmas Bandar Kidul of Kediri. Kegel execises should be done on healing perineal wound. Keywords : Kegel exercises, Primigravida, Degree of rupture perineum